PERANCANGAN MEDIA PEMBELAJARAN EDUKASI BERTEMAKAN TATA SURYA UNTUK SISWA KELAS IX (SEMBILAN) - Rizki Pribadi; Rian Andrian; Suprih Widodo; Rizki Hikmawan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
The material and characteristics of learning Natural Sciences (IPA) are very different from other disciplines. The scope of material in scientific subjects is very broad and closely related to everyday life. The monotonous science learning process will certainly reduce students' motivation and interest in learning. Therefore, there is a need for innovation and learning through the use of methods and optimizing the use of media. One of the technological innovations available to teachers is interactive learning media. The research method used in the design of in-active learning media in science subjects for class XI (nine) is the Research and Development (RnD) research method. In addition, the development model used by researchers in this study is the Analyze, Design, Develop, Implement, Evaluate (ADDIE) model. The results of this study are interactive multimedia-based learning media made with the help of Adobe Flash Professional CS6. The resulting learning media has been tested using the type of black-box testing and is declared to be appropriate for all functions and can be used properly.